Choroidal metastases from thoracic cancer: a retrospective study on clinical characteristics and treatment efficacy - Lin, Xiacheng; Zhong, Yusheng; Li, Haiping; Yang, Yating; Liu, Ahui; Shi, Yajing; Liang, Jianhong; Cheng, Yong (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to examine the clinical characteristics of choroidal metastases (CMs) and assess the efficacy of various treatment strategies for CMs in a specific patient cohort.MethodsThis retrospective case series study included 32 patients (38 eyes) diagnosed with CM at the Department of Ophthalmology, Peking University People’s Hospital, between 2009 and 2022. The cohort included 10 male patients (10 eyes) and 22 female patients (28 eyes), with a mean age of 52.53 ± 10.81 years. Detailed medical histories and multiple ophthalmic examinations were performed for all patients, with diagnoses confirmed by two senior ophthalmologists. Clinical characteristics, treatment responses, and follow-up outcomes were analyzed.ResultsLung cancer was the most common primary tumor (53.1%), with six patients initially presenting with ocular symptoms. Initial ultrasound imaging revealed a mean tumor height of 3.02 mm and a mean basal diameter of 11.09 mm. Optical coherence tomography (OCT) revealed irregular, highly reflective foci with undulating anterior surfaces, and fluorescein angiography (FFA) revealed early choroidal tumor masking and late-phase mottled hyperfluorescence with occasional leakage. Indocyanine green angiography (ICGA) revealed hypofluorescence in early and late phases, with slightly mottled hyperfluorescence in the late phase. The follow-up period ranged from 3 months to 4 years (median 4 months), during which systemic and local treatments effectively controlled or delayed tumor progression in most patients.ConclusionLung and breast cancers are the leading sources of CMs, with bilateral or multifocal lesions more frequently linked to breast cancer. Treatment for CMs should be meticulously individualized and should take into account the patient’s overall condition, tumor burden, and precise tumor location. Local treatment is essential for patients with significant ocular symptoms. A combination of local and systemic treatments has been shown to lead to a more significant reduction in tumor burden.